2010
DOI: 10.1074/jbc.m110.142117
|View full text |Cite
|
Sign up to set email alerts
|

Myosin VI Is Differentially Regulated by DNA Damage in p53- and Cell Type-dependent Manners

Abstract: Myosin VI is an unconventional motor protein and functions in a variety of intracellular processes such as cell migration, vesicular trafficking, and homeostasis of the Golgi complex. Previously, we found that myosin VI is up-regulated in RKO, LS174T, and H1299 cells by DNA damage in a p53-dependent manner and mediates the pro-survival function of p53. Here, we showed that the levels of myosin VI protein were markedly inhibited in MCF7 and LNCaP cells by topoisomerase I-II inhibitors. However, the levels of my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…To maintain this complex at the appropriate functional level may be particularly important, because significantly reduced expression of Runx2 level will not only suppress osteoblast differentiation, but also result in a cell entering the senescent stage. This is consistent with previous published evidence showing that Runx2 interacts with histone deacetylase 6 to repress the p21 gene, known as a downstream effecter of p53 that is associated with cell senescence [30] Moreover, it has been shown that myosin VI DNA damage is p53-dependent [31]. Consuming BB early in life contributes to development or maintenance of the myosin-dependent Runx2 shuttle, and this may also be important to preserve the ability of mesenchymal stromal cells to differentiate into functional osteoblasts later in life under inappropriate stress.…”
Section: Discussionsupporting
confidence: 93%
“…To maintain this complex at the appropriate functional level may be particularly important, because significantly reduced expression of Runx2 level will not only suppress osteoblast differentiation, but also result in a cell entering the senescent stage. This is consistent with previous published evidence showing that Runx2 interacts with histone deacetylase 6 to repress the p21 gene, known as a downstream effecter of p53 that is associated with cell senescence [30] Moreover, it has been shown that myosin VI DNA damage is p53-dependent [31]. Consuming BB early in life contributes to development or maintenance of the myosin-dependent Runx2 shuttle, and this may also be important to preserve the ability of mesenchymal stromal cells to differentiate into functional osteoblasts later in life under inappropriate stress.…”
Section: Discussionsupporting
confidence: 93%
“…In the nucleus, MVI was found in chromatin-free regions, where it was associated with the RNA polymerase II transcription machinery indicating its potential involvement in gene transcription [ 25–27 ]. This notion was also confirmed by the studies demonstrating involvement of MVI in the p53-dependent pro-survival pathway [ 25 , 28 ] and suggesting its modulatory role in androgen-dependent gene expression [ 29 ]. Recently, it has been shown that this molecular motor regulates gene pairing and transcriptional pause release in T cells [ 30 ].…”
Section: Introductionsupporting
confidence: 55%
“…Of note, it is interesting why colocalization with PML bodies does not depend on cell stimulation. It should be recalled that other groups showed involvement of MVI in RNAPII activity, p53-dependent DNA damage and chromosome pairing [ 27 , 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the functional consequences of MYO6 overexpression in colon cancer cells, where it appears to have pro-growth and pro-survival activities ( Figure 2 ) [ 57 ]. The pro-survival activity of this motor is conserved among various cancer types and such MYO6 activity could be linked to stabilization and activation of p53 [ 137 , 138 ]. Furthermore, cell-growth promotion by MYO6 is associated with its known interactions with RNA polymerase II in the nucleus and stimulation of mRNA transcription [ 134 , 135 ], although the causal connection of this mechanism to cancer growth has not been investigated.…”
Section: Unconventional Myosinsmentioning
confidence: 99%